Optimization Of Data Interoperability Between Simrs And The JKN Mobile Application As An Effort To Digital Transform Health Services At Welas Asih Regional Hospital - Ma’rifatulloh, Rizqi; Setiatin, Sali (Jurnal Kesmas Prima Indonesia, 2026)
Digital transformation in Indonesia's healthcare sector is increasingly developing through the implementation of information system integration that supports accelerated service delivery, particularly in healthcare facilities with high visitor loads. This study analyzes the dynamics of interoperability between the Hospital Management Information System (SIMRS) and the JKN Mobile application in the patient registration process at Welas Asih Regional Hospital, a hospital with approximately 2,000 daily visits, of which approximately 1,500 use JKN Mobile. This study used a qualitative approach with a case study design, through in-depth interviews and direct observation of the registration process. The results indicate that the SIMRS–JKN Mobile integration is effective when the system is functioning normally, characterized by a fast barcode check-in process, automatic queue number synchronization without re-input, and consistent receipt number locking across all service stages up to claims. However, several obstacles still arise, particularly BPJS server disruptions, internet network instability, GPS reading issues, and limited patient digital literacy. Staff overcome these obstacles through adaptive strategies such as GPS calibration, switching to the hospital's Wi-Fi network, arrival time validation, and the use of the SIMRS approval feature. This study demonstrates that successful interoperability is determined not only by technological readiness but also by organizational readiness, staff operational competence, and patient capability in using digital applications. These findings provide a novel scientific contribution by providing comprehensive field evidence on the implementation of interoperability in high-volume healthcare facilities and providing recommendations for technical improvements and service governance for hospitals and policymakers.